2020
DOI: 10.15283/ijsc20033
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of p21 Has Inhibitory Effect on Human Hematopoiesis by Blocking Generation of CD43+ Cells via Cell-Cycle Regulation

Abstract: Background and Objectives: p21, an important member of the Cip/Kip family, is involved in inhibitory effects of RUNX1b overexpression during the early stage of human hematopoiesis. Methods and Results: We established a human embryonic stem cell (hESC) line with inducible expression of p21 (p21/hESCs). Overexpression of p21 did not influence either mesoderm induction or emergence of CD34+ cells, but it significantly decreased the production of CD43+ cells and changed the expression profile of hematopoiesis-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…However, HSYA treatment was able to rescue these defects. At the molecular level, we found that HSYA decreased the expression of P53 and the proapoptotic factors Bax and Caspase3 and also inhibit the excessive expression of P21, which is a cyclin‐dependent kinase inhibitor involved in cell cycle arrest 47,48 . Nevertheless, it is also possible that HSYA has P53‐independent roles in hematopoiesis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, HSYA treatment was able to rescue these defects. At the molecular level, we found that HSYA decreased the expression of P53 and the proapoptotic factors Bax and Caspase3 and also inhibit the excessive expression of P21, which is a cyclin‐dependent kinase inhibitor involved in cell cycle arrest 47,48 . Nevertheless, it is also possible that HSYA has P53‐independent roles in hematopoiesis.…”
Section: Discussionmentioning
confidence: 92%
“…At the molecular level, we found that HSYA decreased the expression of P53 and the proapoptotic factors Bax and Caspase3 and also inhibit the excessive expression of P21, which is a cyclin‐dependent kinase inhibitor involved in cell cycle arrest. 47 , 48 Nevertheless, it is also possible that HSYA has P53‐independent roles in hematopoiesis. For example, previous studies suggested that HSYA could increase the nuclear accumulation of β‐catenin 49 and inhibit the activation of NLRP3 inflammasome, 50 both of which play pivotal roles in hematopoiesis physiology.…”
Section: Discussionmentioning
confidence: 99%
“…At the early stage of AGM-S3 co-culture, overexpression of P18 and P21 had opposing effects on the proportions of cells in S and G2/M, but similar inhibitory effects on hematopoietic differentiation. All of these effects could be counteracted by inhibition of TGF-β signaling, as in the case of RUNX1b 1 , 29 . Overexpression of any of these genes increased the proportion of cells in G0/G1, indicating that TGF-β signaling plays a key role in G1 arrest.…”
Section: Discussionmentioning
confidence: 99%
“…These systems are useful to identify the function of critical genes in normal or abnormal hematopoiesis. For example, the AGM-S3 co-culture system could be used to check the detailed cellular and molecular mechanism of hematopoiesis influenced by the critical gene ( Chen et al, 2017 ; Zeng et al, 2020 ). It also has potential utility in screening for compounds that promote human hematopoiesis, which is possible to set up a high throughput screening system for compound function screening using the AGM-S3 co-culture system ( Chang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%